Учет характеристик коммутаторов при анализе и синтезе разрядных цепей высоковольтных импульсных испытательных устройств - Петков, Александр Александрович (НТУ "ХПИ", 2008)
В работе рассмотрены вопросы анализа и синтеза разрядных цепей высоковольтных импульсных испытательных устройств с учетом нелинейности коммутатора. Приведены аналитические соотношения, учитывающие вольтсекундную характеристику, представленную спадающей экспоненциальной зависимостью.

In the work, problems of analysis and synthesis of discharge circuits of high-voltage pulse test devices are considered adjusted for nonlinearity of switchboards. Analytical relations taking into account a volt-second characteristic represented by a declining exponential dependence are presented.
Allowance for switchboard characteristics under analysis and synthesis of discharge circuits of high-voltage pulse test devices
Keywords: высоковольтные импульсные устройства; коммутаторы; импульсы тока; накопители энергии; энергетический баланс; электрическое напряжение; high-voltage pulse test device; discharge circuit; switchboard nonlinearity; analysis; synthesis